Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of "Challenges in operationalizing the water–energy–food nexus"*. Issue 12 (10th September 2018) - Cudennec, C.; Liu, J.; Qi, J.; Yang, H.; Zheng, C.; Gain, A. K.; Lawford, R.; de Strasser, L.; Yillia, P. T.
ABSTRACT: We thank the authors, Varis and Keskinen, and Nauditt, for their constructive contributions. We endorse their key comments, further referring to recent literature and events, including the UN 2018 High Level Political Forum on sustainable development. Here, we elaborate on the epistemological perspective of the water–energy–food nexus conceptualization, assessment, discourse and operationalization.